A26 PEDIATRIC-ONSET INFLAMMATORY BOWEL DISEASE INCREASES THE RISK OF VENOUS THROMBOEMBOLISM: A CANGIEC POPULATION-BASED STUDY. (26th February 2020) - Kuenzig, E; Singh, H; Bitton, A; Kaplan, G G; Carroll, M W; Otley, A; Stukel, T A; Spruin, S; Nugent, Z; Tanyingoh, D; Cui, Y; Filliter, C; et al.
Abstract: Background: Inflammatory bowel disease (IBD) increases the risk of venous thromboembolism (VTE) in patients of all ages but the risk of VTE among Canadian children with IBD has not previously been investigated. Aims: Report the incidence of VTE and subtypes pulmonary embolism (PE) and deep vein thrombosis (DVT) in children with and without IBD. Methods: Children diagnosed with IBD <16y were identified from health administrative data in Ontario (2002–2014), Alberta (2007–2015), and Nova Scotia (2002–2012) using validated algorithms and matched by age and sex to children without IBD (1:5 ratio). Validated ICD-10 codes identified hospitalizations for incident VTE (DVT, PE, and sinovenous thrombosis). Province-specific 5-year cumulative incidence per 1000 person-years (PY) of VTEs were pooled using fixed-effects generalized linear mixed models with a Freeman-Tukey double arcsine transformation. Incidence rate ratios (IRR) within 5 years of diagnosis were pooled using fixed-effects generalized linear mixed models to compare children with and without IBD, and children with Crohn's disease (CD) and ulcerative colitis (UC). Results: 3127 children with IBD (1826 CD; 1045 UC) were matched to 15, 635 children without IBD. The cumulative incidence of VTE within 5 years of IBD diagnosis was 2.8 (95% CI 2.1–3.8) per 1000 PYs compared to 0.13 (95% CI 0.07–0.24) per 1000 PYs in children without IBD (Table). The 5-year cumulative incidences of VTE, DVT, and PE were significantly higher in children with IBD than in children without IBD (VTE: IRR 21.44, 95% CI 10.73–42.82; DVT: IRR 25.15, 95% CI 11.12–56.89; PE: IRR 4.01, 95% CI 1.22–13.18). Compared to UC patients, children with CD were at lower risk of VTE (IRR 0.53, 95% CI 0.29–0.96) and numerically, but not statistically, lower risk of DVT (IRR 0.59, 95% CI 0.30–1.14). Conclusions: Although VTEs are relatively rare among children with IBD, these children are at much greater risk than children without IBD. Gastroenterologists caring for these patients should be cognizant of VTE risk and provide appropriate prophylaxis to those at high risk of VTE. Funding Agencies: CCC